Pantoea ananatis in Oryza sativa in Brazil Pantoea ananatis em Oryza sativa no Brasil - Santos A.N.M.R.* (2023)
© 2023, Universidade Federal de Santa Maria. All rights reserved.The state of Santa Catarina is the second-largest producer of rice seeds in Brazil. Research on phytopathogenic bacterias in this crop is scarce and the high frequency of panicle diseases leads to the hypothesis that seeds may be infected by bacteria. This research quantified the incidence of bacteria in the seeds, verified the bacteria viability during the storage period and characterized the associated bacteria. Seeds from the 2018/19 and 2019/20 seasons were analyzed. To check the incidence, the seeds were disinfected, plated on a nutrient agar + fungicide culture medium, and incubated for seven days at 27 °C. To assess viability, every 45 days, three cultivars stored in a processing unit were subjected to the same detection methodology. To characterize, prevalent colonies were isolated on semi-selective culture medium Pantoea genus-specific agar (PGSA), where the ones that showed growth were subjected to deoxyribonucleic acid (DNA) extraction and Polymerase Chain Reaction (PCR), DNA sequencing, and sequence comparison on GenBank. The hypersensitivity reaction (HR) in tobacco was performed using a bacterial suspension of each isolate. All seed samples had an average incidence of 83%. During storage, the seeds maintained stable bacterial viability, with an average incidence of 95% at the beginning of storage and 99% at the end of it. All isolates that grew in PGSA culture medium were identified by molecular characterization with 100% identity with two specimens of Pantoea ananatis and one of them induced RH in tobacco.